The Influence of Organizational Culture and Remuneration on Employee Performance at the Ministry of Health's Health Polytechnic in Surabaya - Purbasari*, Fitri; Kustiningsih, Nanik; Rahayu, Sri (Universitas Syiah Kuala, 2024)
Employee performance can be seen as a service provided by individuals or groups within an institution to fulfill service needs. The aim is to enhance the welfare of the institution and the target served. In government institutions, remuneration is an inseparable aspect. This research aims to analyze the influence of organizational culture and remuneration on employee performance at the Health Polytechnic of the Ministry of Health in Surabaya. The research method used is quantitative descriptive, with data analysis employing multiple linear regression statistical tests, classic assumptions, hypothesis testing, and determination coefficient. The sampling technique involved simple random sampling with a total of 81 respondents employed at the Health Polytechnic of the Ministry of Health in Surabaya.